FLOW DIAGRAM OF COMPUTER TRAINER COMPLEX OF OPERATORS OF GAS PUMPING OVER AGGREGATES GPA-TS1-16C - Матвієнко, Роман Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Necessity of creation of computer trainer complexes for a study and preparation of operators of difficult technological objects is mentioned, a structure of computer trainer complex for a study and verification of readiness of operators GPA, and also method of work with an aforementioned trainer complex are resulted.